A modified branch line coupler with compact size and ultra wide harmonics suppression band. Issue 5 (4th July 2022) - Alizadeh, Samireh; Roshani, Saeed; Roshani, Sobhan
ABSTRACT: In microstrip branch line coupler (BLC) design, there are significant parameters, including size reduction, insertion loss, and harmonic suppression, which affect the performances of the device. In this paper, a modified BLC with compact size, wide harmonics suppression band, and low insertion loss in operating band is designed. In the proposed design, four types of resonators are used together to create proposed BLC with superior performance. The proposed BLC works at 900 MHz with only 0.1 dB insertion loss at pass band. The proposed BLC provides wide harmonics rejection band from 1.8 to 8.1 GHz, which suppresses 2nd to 9th unwanted harmonics. The conventional coupler occupies 0.25 λ × 0.25 λ, which has undesirable size. But, the proposed BLC occupies compact area of only 21.95 mm × 30.55 mm (0.12 λ × 0.09 λ), which shows more than 81% size reduction.